Can athletes favorably alter body composition with ephedrine, caffeine and aspirin? - Prevost, M. C. (The Journal of Performance Enhancement, 1999)
The sympathetic nervous system plays a direct role in the control of thermogenesis and the control of energy balance in the body. Evidence indicates that some cases of obesity may be due in part to an inadequate sympathetic tone. The sympathetic agonists ephedrine, caffeine and aspirin have been studied extensively to determine the feasibility of using these agents to correct for an inadequate sympathetic tone in obese individuals. Ephedrine alone is fairly ineffective as an anorectic and thermogenic agent. However, the addition of caffeine or caffeine and aspirin greatly enhances both the anorectic and thermogenic properties of ephedrine. The combination has been shown to be effective at producing weight loss and preserving muscle mass in animals and in obese adults on low calorie diets. Most of the weight loss can be accounted for by anorectic effects but thermogenic effects play a role as well. The combination is well tolerated in controlled research studies. However, the FDA is concerned about the over the counter sale of ephedrine following a large number of reports concerning adverse reactions. Because all of the research has been performed on animals or obese adults it is difficult to say if ephedrine, caffeine and aspirin would be beneficial to athletes trying to alter body composition.